Caracterización y tipificación de fincas productoras de cacao (Theobroma cacao L.) Nacional y CCN51 en el Cantón Ventanas - Los Ríos, Ecuador - Suárez Basante, Génesis Lissette (2019)
This research work was carried out through the application of surveys with 67 questions to a representative sample of 170 producers of National Cocoa and CCN51 in various sectors of the Ventanas Canton, in order to collect information and identify the characteristics of the farmers and in turn the real problems they face on a daily basis; due to the fact that we currently do not find recorded information on the agricultural activities of the cocoa sector. The purpose of this work was the development and use of indicators and sub-indicators to determine the characterization and typification of cocoa-producing farms in the Ventanas Canton. The use of these indicators allows us to analyze the ecological and socio-cultural economic situation and conditions of small and medium-sized cocoa producers. In the economic indicator 47% of the producers their monthly net income is $ 401 with the production obtained in the farms. In the ecological indicator the producers are affected by the disease monilla. In the sociocultural indicator, it can be highlighted that 80% of the producers enjoy some basic services, including electric energy, while 42% of the producers are between 41 and 60 years old. It is concluded that most producers have a basic level of education that is directly linked to the production process and farm work. The results achieved seek to contribute information and at the same time knowledge of how to work in the agricultural sector